2003
DOI: 10.1083/jcb.200206079
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase activates Rac by entering in a complex with Eps8, Abi1, and Sos-1

Abstract: Class I phosphoinositide 3-kinases (PI3Ks) are implicated in many cellular responses controlled by receptor tyrosine kinases (RTKs), including actin cytoskeletal remodeling. Within this pathway, Rac is a key downstream target/effector of PI3K. However, how the signal is routed from PI3K to Rac is unclear. One possible candidate for this function is the Rac-activating complex Eps8–Abi1–Sos-1, which possesses Rac-specific guanine nucleotide exchange factor (GEF) activity. Here, we show that Abi1 (also known as E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
238
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(245 citation statements)
references
References 29 publications
6
238
0
1
Order By: Relevance
“…Tyrosine phosphorylation of c-Cbl and interaction of c-Cbl with PI3K are indispensable for c-Cbl-dependent signaling that leads to cytoskeletal effects in v-Abl-3T3 fibroblasts (Feshchenko et al, 1999;Teckchandani et al, 2001Teckchandani et al, , 2005b. Furthermore, functions of PI3K and several proteins that may act downstream of c-Cbl in this system have been shown to require their membrane localization (Abassi and Vuori, 2002;Innocenti et al, 2003;Arthur et al, 2004). Together, these findings suggested that tyrosine phosphorylation of c-Cbl may play a role in mediating its membrane SLAP enhances c-Cbl-mediated cell spreading and adhesion G Swaminathan et al localization in v-Abl-3T3 cells.…”
Section: Discussionmentioning
confidence: 98%
“…Tyrosine phosphorylation of c-Cbl and interaction of c-Cbl with PI3K are indispensable for c-Cbl-dependent signaling that leads to cytoskeletal effects in v-Abl-3T3 fibroblasts (Feshchenko et al, 1999;Teckchandani et al, 2001Teckchandani et al, , 2005b. Furthermore, functions of PI3K and several proteins that may act downstream of c-Cbl in this system have been shown to require their membrane localization (Abassi and Vuori, 2002;Innocenti et al, 2003;Arthur et al, 2004). Together, these findings suggested that tyrosine phosphorylation of c-Cbl may play a role in mediating its membrane SLAP enhances c-Cbl-mediated cell spreading and adhesion G Swaminathan et al localization in v-Abl-3T3 cells.…”
Section: Discussionmentioning
confidence: 98%
“…Although we have yet to identify the mechanism by which ⌬p85 inhibits Rac-1, cell type-specific factors may be important. Recent findings indicate that p85 activates Rac-1 by associating with a multiprotein complex (including Eps8, Abi1, and SOS-1) that binds to p85 SH2 domains (38). We hypothesize that, in certain cell types, the p85 inter-SH2 domain is also required for Rac-1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…p85␣ associates with Rac-1, an upstream activator of JNK, and activates Rac-1 through association with a multiprotein complex that binds to p85 SH2 domains (38). We investi- Ad5-CMV or treated with medium alone (Ϫ).…”
Section: Pi3k-dependent Pathway Contributes To Nsclc Cellmentioning
confidence: 99%
“…We found that somatostatin does not directly affect PI3-K activity, but potently interferes with the Rac activation induced by PDGF, thus suggesting that it acts on the pathway between PI3-K and Rac. This pathway has been recently investigated (but not totally clarified) and implies the involvement of Rac-specific guanine nucleotide exchange factors such as Vav, Tiam-1, and Sos-1, which generally form multi-molecular complexes with other proteins (32,33,34). Future studies are necessary to identify the molecular target of somatostatin along this route.…”
Section: Somatostatin Inhibits Pdgf-induced Rac Activation In Sh-mentioning
confidence: 99%